Leader‐following coordination problem with an uncertain leader in a multi‐agent system. Issue 10 (1st July 2014) - Tang, Yutao
Abstract : A leader‐following coordination problem is considered in this study where the active leader is driven by an unknown input. With the help of output regulation and disturbance decoupling, a distributed protocol is proposed to solve this problem. Two cases are studied based on whether the bound of uncertain (disturbance) inputs of the leader is known. When the bound is unknown, an adaptive technique is employed to achieve the goal. Simulations are also given to verify the effectiveness of these controllers.